Testing Basic Assumptions Reveals When (Not) to Expect Mindset and Belonging Interventions to Succeed. (October 2020) - McPartlan, Peter; Solanki, Sabrina; Xu, Di; Sato, Brian
In this case study, we investigated the effectiveness of growth mindset and social belonging interventions in a college setting with large numbers of traditionally underrepresented groups (n = 1, 091). In doing so, we highlight the characteristics of the students in our study that are important for determining whether we should expect such interventions to be effective for diverse higher education populations. Correlational analyses revealed no evidence that growth mindset or social belonging were barriers to academic success among targeted subgroups in our sample. Additionally, we found no evidence that underrepresented minority, first-generation, or low-income students substantially endorsed fixed mindset or belonging uncertainty measures at baseline. We discuss benefits of testing basic assumptions for interpreting null results, including choosing the most appropriate interventions, accurately identifying subgroups who face psychological barriers to academic success, and establishing "redundancy thresholds" at which messages do not need to be reinforced by interventions.